2016
DOI: 10.7717/peerj.2432
|View full text |Cite
|
Sign up to set email alerts
|

Food safety in Thailand 4: comparison of pesticide residues found in three commonly consumed vegetables purchased from local markets and supermarkets in Thailand

Abstract: BackgroundThe wide use of pesticides raises concerns on the health risks associated with pesticide exposure. For developing countries, like Thailand, pesticide monitoring program (in vegetables and fruits) and also the maximum residue limits (MRL) regulation have not been entirely implemented. The MRL is a product limit, not a safety limit. The MRL is the maximum concentration of a pesticide residue (expressed as mg/kg) recommended by the Codex Alimentarius Commission to be legally permitted in or on food comm… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 26 publications
4
34
0
Order By: Relevance
“…However, the observed trend was not shown to be statistically significant ( r = −.547, p = .082). The trend of pesticide removal efficiency by washing being related with their water solubility properties, is consistent with the findings of previous studies (Kong et al, ; Wanwimolruk et al, ). However, washing guava fruit with the running water method did not seem to be the effective way to remove the pesticide residues from guava fruits.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, the observed trend was not shown to be statistically significant ( r = −.547, p = .082). The trend of pesticide removal efficiency by washing being related with their water solubility properties, is consistent with the findings of previous studies (Kong et al, ; Wanwimolruk et al, ). However, washing guava fruit with the running water method did not seem to be the effective way to remove the pesticide residues from guava fruits.…”
Section: Discussionsupporting
confidence: 92%
“…Such a large number of pesticides (18 types, Figure ) detected in the guava samples is unexpected as this has not previously been reported in other fruits and vegetables sold in Thailand. For instance, 10–12 pesticides were detected in Chinese kale, pakchoi, morning glory, cabbage, and tomato (Wanwimolruk, Duangsuwan, Phopin, & Boonpangrak, ; Wanwimolruk, Kanchanamayoon, Phopin, & Prachayasittikul, ; Wanwimolruk, Phopin, Boonpangrak, & Prachayasittikul, ). Eight pesticides were found in Thai mangosteen fruit (Phopin, Wanwimolruk, & Prachayasittikul, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A er numerous allegations of excessive carbofuran in watermelon and durian from ailand, Wanwimolruk et al [10] examined these products in the market across eight provinces declaring that the residue was lower than the recommended MRL value, posing no risk of contamination. e coworkers further investigated the presence of carbofuran and other pesticides in the commonly consumed vegetables; carbofuran was occasionally detected at a level higher than the MRL [10,11]. In another study by Chowdhury et al [12], carbofuran residue was reported above the MRL value in some eggplants sampled from Bangladesh markets.…”
Section: Introductionmentioning
confidence: 99%